2014
DOI: 10.1002/humu.22537
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Copy Number Variation Detection Tools from Whole-Exome Sequencing Data

Abstract: Copy number variation (CNV) has been found to play an important role in human disease. Next-generation sequencing technology, including whole-genome sequencing (WGS) and whole-exome sequencing (WES), has become a primary strategy for studying the genetic basis of human disease. Several CNV calling tools have recently been developed on the basis of WES data. However, the comparative performance of these tools using real data remains unclear. An objective evaluation study of these tools in practical research sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
210
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(231 citation statements)
references
References 46 publications
16
210
0
2
Order By: Relevance
“…While XHMM utilizes the principal component analysis followed by the Hidden Markov model to identify CNVs, CoNIFER uses a singular value decomposition technique to correct systematic biases and identifies a CNV call if the corrected signal reaches a predefined threshold at no less than three subsequent exons (Fromer et al, 2012;Krumm et al, 2012). Breakpoint detection is an advantage of the XHMM (Fromer et al, 2012;Tan et al, 2014). According to our data, XHMM showed more reliable results for the size of the OTOA deletion.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…While XHMM utilizes the principal component analysis followed by the Hidden Markov model to identify CNVs, CoNIFER uses a singular value decomposition technique to correct systematic biases and identifies a CNV call if the corrected signal reaches a predefined threshold at no less than three subsequent exons (Fromer et al, 2012;Krumm et al, 2012). Breakpoint detection is an advantage of the XHMM (Fromer et al, 2012;Tan et al, 2014). According to our data, XHMM showed more reliable results for the size of the OTOA deletion.…”
Section: Discussionmentioning
confidence: 73%
“…We also noted that CoNIFER CNV analysis missed two heterozygous deletions used as positive controls. Recent CNV comparison studies in WES showed that by using the previously described heterozygosity check method (Zhu et al, 2012), CoNIFER detects less (40%) heterozygous false-positive deletions (for regions > 1 kb) compared to XHMM (64%) (Tan et al, 2014), suggesting that it might be missing some true positives to increase specificity. Conservative predefined thresholds in default settings of the CoNIFER might be the reason for missing heterozygous deletions in positive controls in our data set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic and research laboratories, whether public or private, therefore tend to search for coding variants, most of which can be detected by WES, first. Such variants can also be detected by WGS, and several studies previously compared WES and WGS for different types of variations and/or in different contexts (9,(11)(12)(13)(14)(15)(16), but none of them in a really comprehensive manner. Here, we compared WES and WGS, in terms of detection rates and quality, for single-nucleotide variants (SNVs), small insertions/ deletions (indels), and copy-number variants (CNVs) within the regions of the human genome covered by WES, using the most recent next-generation sequencing (NGS) technologies.…”
mentioning
confidence: 99%
“…Identification of somatic and germline mosaic events or copy number variants remain complicated despite the progress made in the field. 31,32 Copy number variants have an important contribution to many Mendelian disorders [33][34][35] and are often overlooked or disregarded in NGS studies. The pathogenic variant can also be unsequenced due to lack of targeting, capturing, or bad mapping quality.…”
Section: Gene Identification Studies In Mendelian Disordersmentioning
confidence: 99%